Extracellular vesicles as a new horizon in the diagnosis and treatment of inflammatory eye diseases: A narrative review of the literature - Habibi, Azam; Zarei-Behjani, Zeinab; Falamarzi, Kimia; Malekpour, Mahdi; Ebrahimi, Fatemeh; Soleimani, Masood; Nejabat, Mahmood; Khosravi, Amir; Moayedfard, Zahra; Pakbaz, Sara; Dehdari Ebrahimi, Niloofar; Azarpira, Negar (Frontiers in Immunology, 2023)
Abstract Extracellular vesicles include exosomes, microvesicles, and apoptotic bodies. Their cargos contain a diverse variety of lipids, proteins, and nucleic acids that are involved in both normal physiology and pathology of the ocular system. Thus, studying extracellular vesicles may lead to a more comprehensive understanding of the pathogenesis, diagnosis, and even potential treatments for various diseases. The roles of extracellular vesicles in inflammatory eye disorders have been widely investigated in recent years. The term "inflammatory eye diseases" refers to a variety of eye conditions such as inflammation-related diseases, degenerative conditions with remarkable inflammatory components, neuropathy, and tumors. This study presents an overview of extracellular vesicles' and exosomes' pathogenic, diagnostic, and therapeutic values in inflammatory eye diseases, as well as existing and potential challenges.